Paleo-Seismicity in the Euganean Hills Province (Northeast Italy): Constraints From Geomechanical and Geophysical Tests in the Schio-Vicenza Fault Area - Martin, Silvana; Fedrizzi, Fabio; Boaga, Jacopo; Cenni, Nicola; Agnini, Claudia; Cortellazzo, Giampaolo; Rossato, Sandro (Frontiers in Earth Science, 2020)
Gouges and cataclasites within exhumed fault zones are valuable indicators of past seismic events. Gouge layers, 40 – 100 cm-thick and decameters long, have been found within uplifted Cretaceous limestones in the Euganean Hills (SW of Padova, NE Italy), Cenozoic sub-volcanic chambers intruded within a Meso-Cenozoic sequence. The main tectonic lineament in the area is the Schio-Vicenza Fault, that bounds the Euganean Hills to the East. Micropaleontological analyses reveal that the gouges derive from the fragmentation and pulverization of the adjacent pristine carbonatic rocks. Stress-tests on specimens from bedrock associated with gouges yielded a minimum dissipated strain energy of 0.3 – 0.5 MJ/m3 to shatter them. Henceforth, additional strain energy was necessary to pulverize these rocks within the gouge zones. GNSS observations show that the present deformation pattern in this region of Italy is a few tens of nanostrain (10 – 30 1/y), not enough to generate such gouge layers. Therefore, the seismicity of the Euganean Hills (currently M≤5) must be reconsidered in the light of the Schio-Vicenza Fault past activity. The gouges may imply that the Schio-Vicenza Fault had a more intense activity in the past, or this area was affected by remote events or tectonic structures. This paper provides new clues on the evolution of the tectonic and morphological setting of the area, with relevant consequences on seismic risk assessment of the nearby urbanized area, including the cities of Padova and Vicenza.